Sebuah Studi Niat Beli Skincare: Pengaruh Social media Marketing, E-WOM, dan In-store Display - Putri, Heristya (Jurnal Ilmu Manajemen, 2021)
Several factors can be used to determine the success of consumer purchase intentions. In this study, the factors that can influence purchase intention are formed from social media marketing, e-commerce, and in-store displays. The purpose of this study was to determine the effect of social media marketing, e-WOM, and in-store displays on purchase intention of skincare products (study on consumers of Rena beauty store-Tuban). This research is quantitative. The sampling technique used was non-probability sampling with judgmental methods. The sample used was 100 people. The respondent in this study has seen the contents of Tiktok owned by Rena beauty store and has never purchased skincare products at Rena beauty store, with an age range of 17-35 years. The measurement scale uses the Likert scale. The measurement method used is a questionnaire, data analysis using multiple linear regression equation models. The data is processed using SPSS version 26. The results of this study indicate that social media marketing has a significant effect on the intention to buy skincare products for consumers in Rena beauty store-Tuban; meanwhile, e-WOM has no significant effect on the intention to buy skincare products for consumers because beauty store-Tuban, the in-store display also does not affect. Significantly on the intention to buy skincare products to consumers of Rena beauty store-Tuban.